Facile synthesis of manganese silicate nanoparticles for pH/GSH-responsive T1-weighted magnetic resonance imaging. Issue 24 (2nd June 2016) - Li, X. W.; Zhao, W. R.; Liu, Y. J.; Liu, X. H.; Shi, P.; Li, Y. S.; Shi, J. L.
Abstract : Manganese silicate nanoparticles were facilely synthesized and showed high potential as T 1 -MRI contrast agents for cancer diagnosis. Abstract : Contrast agents (CAs) play an important role in enhancing the magnetic resonance imaging (MRI) performance for accurate tumor diagnosis, which, however, may give rise to unexceptional issues such as in vivo accumulation and bio-toxicity. Here we report on manganese silicate nanoparticles (denoted as MnSNs) as highly biocompatible and pH/GSH-responsive T 1 -weighted MRI CAs. The MnSNs were synthesized via a facile, cost-effective and environmentally friendly route based on one-step rapid precipitation between the Mn 2+ cation and the SiO3 2− anion in aqueous solution at room temperature without any other additives, and showed excellent dispersion stability in water or PBS for weeks without any surface modification at ambient temperature. The MnSNs present an efficient pH/GSH-responsive T 1 -MRI feature based on the rapid changes in the relaxation rate in a mildly acidic/reducing environment both in vitro and in vivo, and furthermore, MnSNs showed negligible cellular cytotoxicity in vitro, no distinct tissue toxicity in vivo and fast clearance from the body organs and tissues in 24–72 h. Thus, the MnSNs are able to serve as a novel class of highly promising T 1 -MRI CAs for clinical cancer diagnosis.